Generalized interest rate dynamics and its impacts on finance and pensions. Issue 1 (2nd January 2017) - Stehlík, Milan; Kiseľák, Jozef; Potocký, Rastislav; Jordanova, Pavlina
ABSTRACT: The recent global financial crisis caused implementation of negative or close to zero interest rates. This situation implies a necessity to study a flexible and simplistic model of interest rate, which well accommodates oscillations, cycles, and negative signs. In this article, we introduce a novel nonlinear stochastic interest rate model, which, as a special case, incorporates the standard linear model of Parker. Many practical implications for finance and pensions are obtained.